Litani - Lourey, Jess, 1970- (Thomas & Mercer, 2021)
In the summer of 1984, 14-year-old Frankie Jubilee is sent to live with her estranged mother in the small Minnesota town of Litani. The locals whisper about "The Game," her mother warns her to stay out of the woods and away from adults, and Frankie begins to wonder if she living among monsters, even in the bright light of day.